2019
DOI: 10.1016/j.jpeds.2018.12.062
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of Brain Injury and Brain Volumes after Posthemorrhagic Ventricular Dilatation: A Nested Substudy of the Randomized Controlled ELVIS Trial

Abstract: Background: There is accumulating evidence showing beneficial effects of early intervention on posthemorrhagic ventricular dilatation (PHVD) and neurologic outcomes. Objective:To compare the effect of early and late intervention for PHVD on brain injury and ventricular volume using term-equivalent age magnetic resonance imaging (TEA-MRI). Methods:In the ELVIS (Early versus Late Ventricular Intervention Study) trial 126 preterm infants ≤34 weeks gestation with PHVD after grade III-IV intraventricular hemorrhage… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
28
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 41 publications
(29 citation statements)
references
References 26 publications
1
28
0
Order By: Relevance
“…Intervention consists of a variety of techniques to drain CSF, including external ventricular drains (EVD), lumbar punctures (LP), and ventricular taps (VT), among others. [11]. In comparison, many North American centres employ a later approach where treatment is initiated depending on the ventricular index and clinical signs (e.g., increased ICP, head circumference, ventricle size, tense fontanelle, etc.)…”
Section: Introductionmentioning
confidence: 99%
“…Intervention consists of a variety of techniques to drain CSF, including external ventricular drains (EVD), lumbar punctures (LP), and ventricular taps (VT), among others. [11]. In comparison, many North American centres employ a later approach where treatment is initiated depending on the ventricular index and clinical signs (e.g., increased ICP, head circumference, ventricle size, tense fontanelle, etc.)…”
Section: Introductionmentioning
confidence: 99%
“…Our group and others [7,9,64] have demonstrated that larger ventricle size at the time of neurosurgical intervention may be associated with worse neurodevelopmental outcome, though this remains controversial and is an area of active study [18,[64][65][66]. Notably, in the current study, the FOHR at temporization was high (0.7 ± 0.07), indicating substantial ventriculomegaly prior to intervention.…”
Section: Plos Onementioning
confidence: 46%
“…Equally, the ELVIS trial (20) has completed its recruitment and later neurodevelopmental outcomes are expected to be published soon. These results are eagerly awaited as a sub-study of the ELVIS trial has reported that, in the high-threshold group (LPs when the VI > p97 + 4 mm and anterior horn width >10 mm), there was more brain injury and higher ventricular volumes compared to the low-threshold groups (VI > p97 and anterior horn width >6 mm) (41). There is also interest surrounding stem cell treatment after sIVH; however, this has only been reported in phase 1 trial (42).…”
Section: Discussionmentioning
confidence: 99%